Republic of Moldova : Staff Report for the 2014 Article IV Consultation and First Post-Program Monitoring Discussions. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper focuses on Moldova's 2014 Article IV Consultation and First Post-Program Monitoring Discussions. Moldova largely achieved the main objectives of the economic program supported by a combined Extended Credit Facility/Extended Fund Facility (ECF/EFF). The country's economic performance was among the strongest in the region during 2010-2013. This was made possible by adequate macroeconomic stabilization measures and ambitious structural reforms implemented in the wake of the crisis under the IMF-supported program. The Moldovan economy recovered strongly from the drought-related contraction of 2012, but activity will significantly slow in 2014 owing to a moderation in agriculture production and related industries and weaker economic activity in main trading partners.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet